Drug Utilization review of monitored parenteral antimicrobials in a tertiary care private hospital in Cebu City - So, Jan Steven P.
Infectious diseases remain as principal determinants of morbidity and mortality in our country due to the advent of drug resistance. Major drivers for AMR may be attributed to indiscriminate prescribing and consumption. AMS programs are established to mitigate the adverse consequences of AMR. Drug use evaluation in hospitals ensures provision of rational medication therapy to patients.